Kesadaran Hukum Masyarakat dalam Jual Beli Tanah Tanpa Akta PPAT Demi Menjamin Kepastian Hukum dan Hak Atas Tanah di Wilayah Kelurahan Fatukoa Kecamatan Maulafa Kota Kupang - Soni Esrayanus Benu; Darius Mauritsius; Husni Kusuma Dinata (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The increasing need for land has made land purchase and sale agreements more and more occurring. The sale and purchase agreement made by agreement must be carried out on the principle of clear cash. However, in practice, there are still many buying and selling that are not in accordance with the principle of light cash and the principle of Nemo plus juris as the principle of land registration. Problems regarding the sale and purchase of land that are not in accordance with procedures, not in accordance with existing principles and even not carried out in front of the authorized officials, namely the Sub-district Head and PPAT, still occur in Fatukoa Village, Maulafa District, Kupang City, resulting in legal uncertainty and land rights on the land object being traded. Uncertainty about the law. The type of research used is empirical legal research, and the data sources taken are primary data, secondary data and tertiary data. The population and samples taken are: 2 sellers, 2 buyers, heirs and the community. The sample used is the saturated sample technique where all members of the population get the same opportunity. The results of the study show that: (1). The authority of the sub-district head in making a letter of release of rights is contained in article 131 Paragraph (3) of the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency No. 3 of 1997 concerning the Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration. Regarding land that is sold and sold without using a PPAT deed, it must be done at the sub-district where the land is located, applicants who want to make SPPHT must follow the existing procedures and procedures starting from the agreement of both parties, the readiness of documents, the creation and implementation of SPPHT, registration to the signing and submission of the land rights release letter. (2) Public awareness of the existing regulations The level of public awareness of fatukoa is still very low. The public really does not understand the importance of registering land rights and the implementation of buying and selling with existing procedures with PPAT deeds or with letters under hand, namely the release of land rights. The factors that hinder the legal awareness of the community in Fatukoa Village are education factors and economic factors.